2023
DOI: 10.1021/acs.chemmater.3c01632
|View full text |Cite
|
Sign up to set email alerts
|

Zn Redistribution and Volatility in ZnZrOx Catalysts for CO2 Hydrogenation

Evgeniy A. Redekop,
Tomas Cordero-Lanzac,
Davide Salusso
et al.

Abstract: ZnO–ZrO 2 mixed oxide (ZnZrO x ) catalysts are widely studied as selective catalysts for CO 2 hydrogenation into methanol at high-temperature conditions (300–350 °C) that are preferred for the subsequent in situ zeolite-catalyzed conversion of methanol into hydrocarbons in a tandem process. Zn, a key ingredient of these mixed oxide catalysts, is known to volatilize from ZnO under high-temperature conditions, but lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…At 400 °C/H 2 , the Zr K-edge (Figure S13a) shows a slight decrease in white-line intensity, indicating a minor loss of oxygen atoms in its local environment, consistent with the formation of oxygen vacancies around Ga. Not surprisingly, a small amount of Hf is found in the catalyst: due to the ubiquitous presence of Hf in Zr ores, the former metal is a common impurity in commercially available Zr precursors. The Hf L 2 -edge XANES spectra of GaZr-21 (Figure S13b) showed no significant variations, suggesting that the Ga content does not change, indicating its higher stability in the ZrO 2 lattice with respect to Zn . Furthermore, the FT-EXAFS fit of the Ga-O first coordination shell shows an increase in its CN number, in parallel with the increase in the T d component (Figure S15).…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…At 400 °C/H 2 , the Zr K-edge (Figure S13a) shows a slight decrease in white-line intensity, indicating a minor loss of oxygen atoms in its local environment, consistent with the formation of oxygen vacancies around Ga. Not surprisingly, a small amount of Hf is found in the catalyst: due to the ubiquitous presence of Hf in Zr ores, the former metal is a common impurity in commercially available Zr precursors. The Hf L 2 -edge XANES spectra of GaZr-21 (Figure S13b) showed no significant variations, suggesting that the Ga content does not change, indicating its higher stability in the ZrO 2 lattice with respect to Zn . Furthermore, the FT-EXAFS fit of the Ga-O first coordination shell shows an increase in its CN number, in parallel with the increase in the T d component (Figure S15).…”
mentioning
confidence: 75%
“…It is noteworthy that the (102) Bragg reflection is not visible in GaZr-21, probably due to crystallite size-induced peak broadening; the tetragonal polymorph is instead confirmed by the presence of the 1s → 4d transition in Zr K-edge XANES spectra (Figure S7). Nevertheless, we have previously shown how accurate use of EXAFS fitting and XANES interpretation could confirm that the ZnZr-X catalyst exhibits a mixed cluster local structure, consisting of ZnO nanoclusters (ø < 50 Å) embedded and chemically bonded to a ZrO 2 matrix. ,, This structural scenario is reflected in the UV–vis spectra (Figure c), which can be qualitatively described as a combination of ZrO 2 and ZnO spectra. It can also be observed that the band gap of the ZnO component shifts to lower energies as the Zn content increases, in line with the reduction of the quantum confinement effect and the previously reported cluster growth …”
mentioning
confidence: 84%
See 3 more Smart Citations